2003
DOI: 10.4049/jimmunol.170.1.520
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of the α4 Integrin/VCAM-1 Pathway in Cerebral Leukocyte Trafficking in Lupus-Prone MRL/faslprMice

Abstract: MRL/faslpr mice are affected by a systemic autoimmune disease that results in leukocyte recruitment to a wide range of vascular beds, including the cerebral microvasculature. The mechanisms responsible for the leukocyte trafficking to the brain in these animals are not known. Therefore, the aim of this study was to directly examine the cerebral microvasculature in MRL/faslpr mice and determine the molecular mechanisms responsible for this leukocyte recruitment. Intravital microscopy was used to assess leukocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
45
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 38 publications
(54 reference statements)
5
45
0
Order By: Relevance
“…Our previous intravital microscopy analyses of P-sel/Fas lpr mice support this hypothesis (28,29). We found that the numbers of rolling leukocytes were reduced, but not completely inhibited, in the skin and brain microvasculature in these mutant mice compared with controls, and significant differences in the numbers of firmly adherent leukocytes were not observed.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Our previous intravital microscopy analyses of P-sel/Fas lpr mice support this hypothesis (28,29). We found that the numbers of rolling leukocytes were reduced, but not completely inhibited, in the skin and brain microvasculature in these mutant mice compared with controls, and significant differences in the numbers of firmly adherent leukocytes were not observed.…”
Section: Discussionsupporting
confidence: 66%
“…suggesting that these adhesion molecules may be functional in promoting inflammatory disease in this mouse model and SLE (28,29). In the present study, we analyzed Fas lpr mice deficient in P-selectin or its major ligand P-selectin glycoprotein ligand-1 (PSGL-1) to determine the roles of these adhesion molecules in IC-mediated SLE-like vascular inflammation.…”
mentioning
confidence: 99%
“…Vascular cell adhesion molecule-1 supports the adhesion of the primary leukocyte populations present in atherosclerotic plaques and may contribute to the quantitative predominance of monocytes over lymphocytes (Gerszten et al, 1998). Vascular cell adhesion molecule-1 facilitates transendothelial entry of circulating monocytes through human brain endothelial cells (MacIntyre et al, 2003), and it plays an important role in leukocyte recruitment in brain diseases, as shown in experimental models of systemic lupus erythematosus (James et al, 2003), and in chronic graft-versus-host disease (Sostak et al, 2004). At the bedside, soluble VCAM-1 concentration in plasma is raised in patients with acute stroke (Blann et al, 1999), and a two-fold increase of this parameter was found independently associated to poor outcome after stroke (Chamorro et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Immunoneutralization of VCAM-1 has also been shown to ameliorate hepatic necrosis and neutrophil infiltration in response to endotoxin (4). Indeed, VCAM-1 appears to be integral to leukocyte recruitment in a variety of tissues, including the brain (10,11), kidney (12), and intestine (13).…”
mentioning
confidence: 99%